Education, Information, and Smoking Decisions : Evidence from Smoking Histories, 1940-2000 - de Walque, Damien (World Bank, Washington, DC, 2013)
The author tests the hypothesis that education improves health and increases people's life expectancy. Smoking histories-reconstructed from retrospective data in the National Health Interview Surveys in the United States-show that after 1950, when information about the dangers associated with tobacco consumption started to diffuse, the prevalence of smoking declined earlier and most dramatically for college graduates. More educated individuals are also more likely to quit smoking: incidence analysis of smoking cessation shows a strong education effect. The instrumental variable approach, which relies on the fact that during the Vietnam War college attendance provided a strategy to avoid the draft, indicates that education does affect decisions about whether to smoke or stop smoking.